Enchancing MSME Product Brand Identity Through Rebranding and Introducing Business Brand Image - Sahyunu Sahyunu (Journal on Education, 2023)
Rebranding business brand identity and introducing business brand image are closely related. Rebranding a strong product brand identity can aid in the introduction of a stronger business brand image, and introducing a stronger business brand image can aid in the strengthening of the product brand identity. This study intends to rebrand UMKM kedai larissa's product brand identity and establish a business brand image because it can help improve product brand identity and introduce a stronger business brand image. This would assist MSMEs achieve greater success in a market that is becoming increasingly competitive. Due to the fragmentation of the culinary MSME business field, the study's findings are the process of rebranding the iconic business logo by altering typefaces, colors, and applying simple, memorable, and classy concepts so that it can become a characteristic of the business brand image. This logo can increase client attention in regards to the larissa shop's brand image expansion.